Cryptococcus neoformans trehalose-6-phosphate synthase (tps1) promotes organ-specific virulence and fungal protection against multiple lines of host defenses - Goughenour, Kristie; Creech, Arianna; Xu, Jintao; He, Xiumiao; Hissong, Rylan; Giamberardino, Charles; Tenor, Jennifer; Toffaletti, Dena; Perfect, John; Olszewski, Michal (Frontiers in Cellular and Infection Microbiology, 2024)
Trehalose-6-phosphate synthase (TPS1) was identified as a virulence factor for Cryptococcus neoformans and a promising therapeutic target. This study reveals previously unknown roles of TPS1 in evasion of host defenses during pulmonary and disseminated phases of infection. In the pulmonary infection model, TPS1-deleted (tps1Δ) Cryptococci are rapidly cleared by mouse lungs whereas TPS1-sufficent WT (H99) and revertant (tps1Δ:TPS1) strains expand in the lungs and disseminate, causing 100% mortality. Rapid pulmonary clearance of tps1Δ mutant is T-cell independent and relies on its susceptibility to lung resident factors and innate immune factors, exemplified by tps1Δ but not H99 inhibition in a coculture with dispersed lung cells and its rapid clearance coinciding with innate leukocyte infiltration. In the disseminated model of infection, which bypasses initial lung–fungus interactions, tps1Δ strain remains highly attenuated. Specifically, tps1Δ mutant is unable to colonize the lungs from the bloodstream or expand in spleens but is capable of crossing into the brain, where it remains controlled even in the absence of T cells. In contrast, strains H99 and tps1Δ:TPS1 rapidly expand in all studied organs, leading to rapid death of the infected mice. Since the rapid pulmonary clearance of tps1Δ mutant resembles a response to acapsular strains, the effect of tps1 deletion on capsule formation in vitro and in vivo was examined. Tps1Δ cryptococci form capsules but with a substantially reduced size. In conclusion, TPS1 is an important virulence factor, allowing C. neoformans evasion of resident pulmonary and innate defense mechanisms, most likely via its role in cryptococcal capsule formation.